2016
DOI: 10.1097/md.0000000000002769
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Serological Antibody Profiles Against Human Papillomavirus Type 16 Antigens as Markers for Early Detection of Cervical Cancer

Abstract: Cervical cancer (CC) is the second most frequent neoplasia among women worldwide. Cancer prevention programs around the world have used the Papanicolaou (Pap) smear as the primary diagnostic test to reduce the burden of CC. Nevertheless, such programs have not been effective in developing countries, thus leading to research on alternative tests for CC screening. During the virus life cycle and in the process toward malignancy, different human papillomavirus (HPV) proteins are expressed, and they induce a host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…Meanwhile, we noted little difference in the frequencies of anti‐HPV16 or 18 L1 antibodies between CIN stages and cervical cancer proper (Table and Table ). In contrast, an increased prevalence of anti‐HPV16 L1 antibody in cervical cancer compared to CIN stages was found in Mexico …”
Section: Discussionmentioning
confidence: 79%
“…Meanwhile, we noted little difference in the frequencies of anti‐HPV16 or 18 L1 antibodies between CIN stages and cervical cancer proper (Table and Table ). In contrast, an increased prevalence of anti‐HPV16 L1 antibody in cervical cancer compared to CIN stages was found in Mexico …”
Section: Discussionmentioning
confidence: 79%
“…To evaluate the serum antibodies against HPV antigens, generated during infection, precancerous lesions and cancer, several laboratory technics have been used, such as the ELISA (enzyme linked immunosorbent assay), western blot, radioimmunoassay (RIA) and more recently, Luminex multiplex. These methods use different antigens such as L1 virus like particles (VLPs) from different HPV types; synthetic peptides from L1, L2, E2, E4, and E7, bacterial recombinant proteins, or in vitro-translated viral antigens [7,69].…”
Section: Humoral Immune Response Against Human Papillomavirus Antigensmentioning
confidence: 99%
“…antibodies for OC [62,91]. In this way, several studies have been carried out and showed that antibodies against E7 have been commonly associated with AC and CC, with prevalence that goes from 45% in the anus [78] and up to 75% in the cervix [62,69], while in the penis, vulva, and vagina, the antibody prevalence was under 15% [79]. In contrast, although serological antibodies against E6 prevalence were high in CC patients by using different tests (from 37 to 44%) [70,86], the association of anti-E6 antibodies with this type of cancer has not been very well defined [70,74,75,88].…”
Section: Humoral Immune Response Against Human Papillomavirus Antigensmentioning
confidence: 99%
See 2 more Smart Citations